Indonesian Leather Handicraft Trade in the International Market: SWOT analysis approach - Donald Crestofel Lantu; Mia Rosmiati; Rendra Chaerudin; Sri Herliana; Nur Lawiyah (Journal of International Conference Proceedings (JICP), 2022)
The leather craft industry is one of the growing industries in Indonesia and is one of the export commodities of the creative industry. The creative industry is an industry that is one of the mainstays in the country's economy. The abundance of animal skin waste is used as a variety of commodities that have a selling value. The focus of this research is to analyze the potential of international trade in leather craft commodities by using a SWOT analysis approach. The purpose of this study is to map the internal and external factors of the international trade in leather crafts, which can be one of the preliminary research and sources of future research. From the results of the desk study and SWOT analysis, it was concluded that the leather craft creative industry has an opportunity in the international market with a market share of 4.4% and is in the 6th position as a leather craft exporter in 2021. Internal and external factors for this leather craft shows that the advantages and disadvantages of this creative leather craft industry can be combined to improve business strategies and studies in future research.